Analysis Of Budget Performance Regional Revenue And Expenditure (APBD) In The Province Of North Sumatra - Beatric Krisnanadayanti Sinaga; Tengku Eka Susilawaty (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
This study aims to evaluate the performance of the Regional Revenue and Expenditure Budget (APBD) of North Sumatra Province during 2021–2024 using financial ratios, namely effectiveness, efficiency, independence, and growth. The data were obtained from APBD reports published by the Directorate General of Fiscal Balance, Ministry of Finance. The findings reveal that the effectiveness ratio of regional revenue declined, shifting from the “very effective” category in 2021– 2022 to “quite effective” in 2023 and “less effective” in 2024. The efficiency ratio of regional expenditure remained consistently below 100%, indicating relatively controlled budget use, although some programs were not fully implemented. Fiscal independence is still low, as the contribution of Local Own-Source Revenue (PAD) to total revenue ranged only between 25–50%, reflecting high reliance on central government transfers. The growth ratio of PAD fluctuated, with a sharp increase in 2022 but a decline in 2023 and 2024. Overall, the APBD of North Sumatra Province demonstrates good expenditure efficiency but faces significant challenges in revenue effectiveness, PAD growth, and fiscal independence.